2011
DOI: 10.1017/s175173111100108x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of including genetic progress in milk yield on evaluating the use of sexed semen and other reproduction strategies in a dairy herd

Abstract: The objective of this study was to explore the importance of including genetic progress in milk yield when evaluating different reproductive strategies in a dairy herd by simulation modeling. The model used in this study was SimHerd V, a dynamic and mechanistic Monte Carlo simulation model of a dairy herd including young stock. A daily increasing trend describing genetic milk yield potential of the sire population was included in the model. The inaccuracy of assuming that replacement heifers have the same (mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…This raises the question as to whether sexed semen is beneficial to farm management. Numerous reports have estimated the economic benefits of sexed semen produced by various strategies in many different countries, including the United States, Denmark, Iran, Ireland, and Japan . In general, the use of sexed semen is expected to have a positive effect on the economics of the farms, maintaining replacement heifers and/or the efficiency of expanding dairy herds, resulting in an improved milk yield.…”
Section: The Economic Benefit Of Sexed Semen In the Cattle Industrymentioning
confidence: 99%
“…This raises the question as to whether sexed semen is beneficial to farm management. Numerous reports have estimated the economic benefits of sexed semen produced by various strategies in many different countries, including the United States, Denmark, Iran, Ireland, and Japan . In general, the use of sexed semen is expected to have a positive effect on the economics of the farms, maintaining replacement heifers and/or the efficiency of expanding dairy herds, resulting in an improved milk yield.…”
Section: The Economic Benefit Of Sexed Semen In the Cattle Industrymentioning
confidence: 99%
“…Replacement heifer price is likely to be a key factor for dairy producers when considering the use of sexed semen, yet will also be strongly affected by the widespread use of sexed semen (De Vries et al, 2008). Ettema et al (2011) demonstrated that ignoring genetic progress when modelling reproductive strategies in a herd leads to the underestimation of the profitability of using sexed semen. The use of sexed semen, particularly on virgin heifers, should increase the rate of genetic gain in seasonal, pasture-based dairy herds.…”
Section: Economics Of Sexed Semen Usementioning
confidence: 99%
“…A reproductive surplus generates opportunities for deciding which cows to breed the replacements from, so it is possible to increase the selection intensity. Hence, in combination with selection, use of sexed semen results in reduced genetic lag relative to the sire population (Ettema et al, 2011;Sørensen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%